(untitled) (Diametros, 2013)
In this paper, I argue that God never intends a human being’s death. The core argument is essentially Thomistic. God wills only the good; and human life is always a good, and its privation always an evil. Thus, St. Thomas holds that “God does not will death as per se intended,” and he gives an account of the act of divine punishment that conforms to this claim. However, some further claims of St. Thomas are in tension with this position – particularly his claims as regards the permissibility of intentional killing by agents of the state. I argue that alternative conclusions on these matters are in fact more harmonious with St. Thomas’s claims about God and God’s willing than are his own.